2022
DOI: 10.1186/s12909-022-03277-y
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of virtual and face-to-face training methods on the quality of healthcare services provided by Kermanshah pre-hospital emergency staff (EMS): randomized educational Intervention trial

Abstract: Background Emergency medical centers are globally one of the most important pillars of pre-hospital care. The most important purpose of this system is to provide satisfactory services in the shortest possible time and in accordance with the modern scientific standards of the world. The present study aimed to compare the effect of virtual and face-to-face training methods on the quality of service provided by Kermanshah pre-hospital emergency personnel, Iran. Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…However, the face-to-face training group had better post-test scores than the virtual training group in all skills. Farahmand Rad et al also concluded that according to the nature of the subject matter, the skills which wanted to be trained, and the conditions of the learners, both methods can be used in education (16). Similarly, other studies demonstrated that continuing education was crucial to nurses (17,18), and nursing education was among the predictors of patient outcomes (19).…”
Section: Discussionmentioning
confidence: 99%
“…However, the face-to-face training group had better post-test scores than the virtual training group in all skills. Farahmand Rad et al also concluded that according to the nature of the subject matter, the skills which wanted to be trained, and the conditions of the learners, both methods can be used in education (16). Similarly, other studies demonstrated that continuing education was crucial to nurses (17,18), and nursing education was among the predictors of patient outcomes (19).…”
Section: Discussionmentioning
confidence: 99%
“…The Covid-19 pandemic has hastened the acceptance of virtual training methods, but there is limited knowledge regarding their effectiveness in facilitating the transfer of training and future job performance (Shahriar et al, 2022;Zakarani et al, 2021). Comprehending the distinct difficulties and advantages linked to virtual training and remote work settings is crucial for creating efficient training measures in the contemporary workplace (Mansoori et al, 2020;Rad et al, 2022).…”
Section: Defining the Research Gapmentioning
confidence: 99%
“…The results revealed that virtual training can be advantageous; however, the absence of in-person communication may impede the acquisition of social and interpersonal abilities. Organizations are advised to integrate virtual training alongside other strategies to tackle these challenges (Abidi et al, 2019;Rad et al, 2022)…”
mentioning
confidence: 99%
“…[6,10,19] For example, in medicine, the costly training of surgical scenarios is increasingly being replaced by VR and AR applications, or in service quality training for preclinical emergency personnel. [20,21] The digitalization trend in teaching also promotes digitalization in further education, which leads to a positive trend in the use of VR and AR assistance systems [6]. In addition to an increased interest in VR in the engineering field, there is also an increase in the use of digital devices within learning and educational offers, as well as in educational research.…”
Section: Application Of Vr and Ar In Industrymentioning
confidence: 99%